Copper alloy strip and preparation method and application thereof

By adjusting the proportion and deformation heat treatment process of Ni, Fe and P elements, the problems of conductivity, strength and stress relaxation resistance of copper alloy strips during processing are solved, and the plate shape is improved and warpage is reduced. It is suitable for high-quality Precision etching and processing copper alloy strips.

CN119120982APending Publication Date: 2024-12-13JINTIAN COPPER GROUP CORP NINGBO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410990662.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2024-12-13

Smart Images

  • Figure CN119120982A_ABST
    Figure CN119120982A_ABST
Patent Text Reader

Abstract

The invention discloses a copper alloy strip as well as a preparation method and application thereof, and the copper alloy strip comprises the following components in percentage by mass: 0.32-1.5 wt% of Ni, 0.05-0.3 wt% of P and the balance of copper and inevitable impurities. Wherein the volume percentage ratio L of the small-angle grain boundary in the strip and the volume percentage ratio H of the large-angle grain boundary in the strip meet the condition that L / H is larger than or equal to 1.5 and smaller than or equal to 2.8. According to the method, a specific deformation heat treatment process is combined, the proportion of large-angle and small-angle grain boundaries in the strip is controlled, the internal stress of the strip is reduced, the plate shape of the strip is improved, and finally the copper alloy strip which is good in stress relaxation resistance, excellent in strength and conductivity, good in plate shape and low in warping is obtained; the copper alloy strip has wide application prospects in preparation of parts such as lead frames and vapor chambers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a copper alloy strip and a preparation method and application thereof. Background Art

[0002] With the development of high performance and high integration of 5G communication equipment, not only the number of pins of the internal integrated circuit lead frame has increased, the lead spacing has become more precise and fine, and the requirements for its conductivity, support and heat dissipation have increased. At present, copper-based alloy strips are the mainstream material for lead frames, and their processing methods mainly adopt stamping or chemical etching. The stamping method has high production efficiency and low requirements for the copper matrix, but it is difficult to process small pins or parts with complex shapes. Moreover, for thinner copper strips (thickness <0.3mm), the copper will warp, deform, crack, etc. after stamping. In addition, stamping lubricant will remain on the surface of the processed parts, and the burrs on the stamping fracture are also longer. In contrast, although the chemical etching method has a more complicated processing process, it is basically stress-free processing, which can realize the production of high-precision and multi-pin lead frames, and its proportion in the processing of lead frames is increasing. However, the etching method has higher requirements on the internal stress, plate shape, surface quality and other properties of copper alloy strips.

[0003] Among all types of copper alloy matrix materials for lead frames, Cu-Fe-P materials have higher conductivity and strength, but poor stress relaxation resistance and high temperature resistance. The pins of lead frames using this material as the matrix are prone to deformation and failure during use. Cu-Ni-P materials not only have higher strength, but also better stress relaxation resistance and bending performance than Cu-Fe-P materials, but their conductivity is slightly worse. Therefore, it is necessary to develop a copper alloy strip that has both characteristics to meet the service conditions of lead frames.

[0004] Publication No. CN117626052A discloses a copper-nickel-phosphorus etched copper alloy and a preparation method thereof. The copper-nickel-phosphorus etched copper alloy provided by the invention comprises the following chemical components by mass percentage: Ni: 0.5-2.0%; Zn: 0.02-0.7%; Fe: 0.05-0.15%; P: 0.05-0.35%; Pb: 0.01-0.2%; Mn: 0.05-0.1%; Te: 0.01-0.04% and the balance of Cu. Although the warpage height of the copper-nickel-phosphorus etched copper alloy provided by the invention is reduced after etching, it does not mention the changes in the electrical conductivity, strength and other properties of the alloy.

[0005] The patent document with publication number CN115287495A discloses a copper alloy strip for a semi-etched lead frame, wherein the mass percentage composition of the copper alloy is Fe: 2.0-3.5%, P: 0.03-0.05%, Zn: 0.05-0.3%, Sn: 0.01-0.05%, Nb: 0.1-0.5%, and the balance is copper and inevitable trace impurities. The invention controls the addition amount of Fe, P, Zn, Sn, and Nb to make the alloy have obvious grain refinement, uniform organization, and isotropic orientation, but the tensile strength and plate shape of the copper alloy strip prepared by the invention are poor.

[0006] In summary, it is of great significance to find a method for preparing copper alloy strips to produce copper alloy strips with excellent properties such as strength, conductivity and stress relaxation resistance and with excellent plate shape and surface quality for preparing parts such as lead frames for etching processing. Summary of the invention

[0007] The object of the present invention is to provide a copper alloy strip having excellent electrical conductivity, strength, stress relaxation resistance and high temperature resistance and good plate shape and a preparation method thereof, so as to be used for the preparation of parts such as lead frames and temperature balancing plates.

[0008] A copper alloy strip comprises the following components in percentage by weight: Ni: 0.32-1.5wt%, P: 0.05-0.3wt%, and the remainder is copper and inevitable impurities; the volume percentage L of the small-angle grain boundaries and the volume percentage H of the large-angle grain boundaries inside the copper alloy strip satisfy: 1.5≤L / H≤2.8, wherein the small-angle grain boundaries are grain boundaries with an orientation difference of adjacent grains less than 15°, and the large-angle grain boundaries are grain boundaries with an orientation difference of adjacent grains greater than 15°.

[0009] The copper alloy strip of the present invention is a Cu-Ni-P material, which not only has high strength, but also has excellent stress relaxation resistance and bending performance. Based on the Cu-Ni-P material, the present invention controls the ratio of large-angle grain boundaries and small-angle grain boundaries in the strip to regulate the internal stress distribution of the strip and improve the plate shape of the strip, thereby preparing an alloy strip with excellent performance, good plate shape and low warping.

[0010] The copper alloy strip of the present invention is mainly used for etching processing, and the purpose of etching processing is to solve the bending deformation of the material caused by the external stress during the stamping process. However, in addition to the deformation of the parts caused by the stamping process, if the strip itself has a poor plate shape and severe warping, the etching process will aggravate the deformation of the material. Therefore, the present invention controls the proportion of high-angle grain boundaries and low-angle grain boundaries inside the material through a specific deformation heat treatment method, thereby reducing the plate shape I value of the strip.

[0011] When 1.5≤L / H≤2.8, the internal stress distribution inside the strip is relatively uniform, and after stress relief annealing, the warping height of the strip etching process is less than 0.06μm. If the L / H ratio is greater than 2.8, the proportion of small-angle grain boundaries is too large. Although the uniformity of internal stress distribution can be improved, the strength of the material will be significantly reduced due to the low dislocation density inside the material; if the L / H ratio is less than 1.5, the strip begins to have local stress concentration problems, causing the material to warp, which is not conducive to etching processing. Therefore, the present invention ultimately controls the volume ratio of small-angle grain boundaries and large-angle grain boundaries to be 1.5≤L / H≤2.8.

[0012] The present invention controls the Ni content to be between 0.32 and 1.5 wt%. In the present invention, the P element can form a precipitate phase with the Ni element. If the Ni element content is less than 0.32 wt%, the precipitate phase formed is small and the precipitation strengthening effect cannot be achieved; on the contrary, when the addition amount of the Ni element is higher than 1.5 wt%, due to the limited P element, the Ni element will be solid-dissolved in the copper matrix and the matrix strengthening effect cannot be achieved.

[0013] The present invention controls the P content to 0.05-0.3wt%. P is a key element of the copper alloy of the present invention. When the P content is lower than 0.05wt%, alloy strengthening cannot be achieved; when the P content is higher than 0.3wt%, the electrical conductivity of the material will significantly decrease.

[0014] Preferably, the copper alloy strip also includes Fe, and the mass percentage of Fe is 0.05-0.15wt%. The Fe element can form a second phase with the Ni element at the grain boundary, and can also react with the Cu element to form a copper-iron compound. The present invention controls the Fe content to 0.05-0.15wt%. When the Fe element content is low, the FeP composite phase at the grain boundary is uneven, and the material is prone to intergranular cracking; when the Fe element content is greater than 0.15wt%, Fe will inhibit the formation of the NiP precipitation phase, and will generate hard and brittle copper-iron compounds, which will reduce the plastic processing performance of the material.

[0015] Preferably, in the copper alloy strip, the mass ratio of Ni+Fe to P is 3.0 to 8.5: 1. In order to ensure precipitation strengthening and the pinning effect of grain boundary precipitation relative to dislocations, achieve the strengthening of the copper alloy, and take into account the electrical conductivity of the material, the present invention requires that the mass ratio of Ni+Fe to P is 3.0 to 8.5.

[0016] The present invention forms a nickel-phosphorus phase and an iron-phosphorus phase composite reinforced copper matrix by adjusting the addition ratio of Ni, Fe and P elements in the alloy, thereby making up for the disadvantage that a single strengthening method cannot take into account the material strength, electrical conductivity and stress relaxation resistance.

[0017] Preferably, the copper alloy strip further comprises Cr, and the mass percentage of Cr is 0.1-0.6wt%. 0.1-0.6wt% of Cr element is added to the copper alloy of the present invention. Cr element is an important aging strengthening element of copper-chromium-zirconium series alloys, and the aging temperature range of the copper alloy of the present invention is close to its aging temperature range, so the addition of Cr element achieves the effect of auxiliary strengthening.

[0018] More importantly, the addition of Cr element is also conducive to improving the high temperature softening temperature of the alloy. The copper alloy strip of the present invention is mainly used for lead frames and temperature absorbing plates for etching processing. The above products all need to be welded, and the addition of Cr element can ensure that the material does not undergo obvious deformation during the welding process.

[0019] Preferably, the copper alloy strip further comprises Mg, and the mass percentage of Mg is 0.06-0.12wt%. 0.06-0.12wt% of Mg element is added to the copper alloy of the present invention. Since etching processing is performed, the plate shape (warpage) of the strip is extremely high. The addition of Mg element can promote the refinement and dispersion of grains in copper, improve the uniformity of the structure, and make the alloy have better plasticity and toughness. Therefore, the addition of Mg element can not only improve the strength of the material, but also reduce the plate shape I value of the strip, laying a foundation for etching processing.

[0020] When the addition amount of Mg is less than 0.06wt%, the grain refining effect is not obvious; when it is higher than 0.12wt%, slag will be generated during casting, forming subcutaneous inclusions of the ingot, resulting in peeling and cracking of the strip. Therefore, the present invention finally selects the mass percentage of Mg element to be 0.06-0.12wt%.

[0021] Preferably, the copper alloy strip has a tensile strength of 600-780 MPa, a conductivity of 60-70% IACS, a high temperature softening temperature of ≥510°C, and an initial stress Rp 0.2 Under the condition of 80% of the stress relaxation rate, after treatment at 120℃ for 1000h, the warpage height is less than 0.06μm.

[0022] The second aspect of the present invention provides a method for preparing the copper alloy strip, comprising the following steps: smelting → semi-continuous casting → hot rolling → rough rolling → first annealing → intermediate rolling → second annealing → finishing rolling → third annealing → finished product rolling → stress relief annealing;

[0023] Wherein, the third annealing is performed in a bell furnace, the annealing temperature is 340-480° C., and the annealing time is 4-10 hours.

[0024] The present invention adopts bell furnace annealing to ensure uniform precipitation of NiP precipitate phase, uniform distribution of FeP composite phase at grain boundary, realize control of grain orientation, promote formation of small-angle grain boundary, thereby controlling volume percentage of large-angle grain boundary within a certain range, making internal stress distribution of strip more uniform. When the annealing temperature is higher than 480°C, the proportion of large-angle grain boundary decreases, and the strength of strip also decreases significantly; when the annealing temperature is lower than 340°C, it is not only not conducive to the precipitation of NiP precipitate phase, but also the proportion of large-angle grain boundary is high, the internal stress of strip is too large, which is not conducive to etching processing.

[0025] Domestic and foreign research results show that there is a positive correlation between the dislocation density of the material and the high-angle grain boundary. When the crystal dislocation slips during processing, due to the large difference in the orientation of the grains in the high-angle grain boundary area, the dislocation will accumulate in this area, resulting in an increase in the dislocation density, and ultimately making the internal stress in this area higher than that in other areas. In the present invention, the inventors increase the proportion of low-angle grain boundaries in the matrix by controlling the processing rate of cold rolling and the process parameters of annealing, and control the volume proportion of high-angle grain boundaries and low-angle grain boundaries in the material, thereby improving the problem of uneven internal stress in the strip.

[0026] Preferably, the order of adding materials for smelting is: first add electrolytic copper plate, then add nickel plate and copper-iron master alloy with required composition, then heat to 1200-1300°C, and after all of them are melted, perform air blowing and deoxidation operation. Then add phosphor copper master alloy and copper chromium master alloy, and finally add copper magnesium master alloy. After the composition meets the requirements, it is ready for casting.

[0027] Preferably, the heating temperature of the hot rolling of the present invention is 800-950°C, the holding time is 2-5h, the total processing rate of hot rolling is greater than 92%, and the final rolling temperature is not less than 680°C. In order to ensure the uniform size of the subsequent grains, the grains inside the strip must be fully recrystallized, and at the same time, the uniform distribution of Cr, Ni, Fe, and P elements must be further promoted to lay the foundation for the subsequent solid solution ~ aging strengthening. Hot rolling must be carried out at a high temperature above 800°C. If the hot rolling temperature is higher than 950°C, the Cr and Fe elements inside the ingot will aggregate, and subsequent cold rolling is prone to cracking. The hot rolling process parameters of copper alloys are closely related to the quality of the product. When the final rolling temperature is too low, the plasticity of the rolled piece is reduced, the deformation resistance is increased, the rolling pass must be increased, and cracks and uneven performance will occur. Therefore, the heating temperature must be guaranteed to be above 800°C to achieve the requirement that the final rolling temperature is not less than 680°C.

[0028] Preferably, the second annealing of the present invention adopts air cushion furnace expansion annealing, the heating temperature is 700-850°C, and the belt speed is 15-30m / min. The expansion annealing adopts thermal convection heating to ensure uniform temperature control during heating and cooling of various parts of the strip. After the annealing treatment, the average grain size of the strip is less than 30μm. When the annealing temperature is lower than 700°C, the solid solution of the elements cannot be guaranteed; when the annealing temperature is higher than 850°C, the strip is prone to deformation and warping, which is not conducive to the subsequent plate shape control.

[0029] Preferably, the processing rate of the intermediate rolling of the present invention is 60% to 85%, and the unit tension range of the unwinding is 60 to 80 N / mm 2 , the winding unit tension range is 80~100N / mm 2 The finishing rate is 30% to 50%, and the unwinding unit tension range is 80 to 90 N / mm 2 , the winding unit tension range is 85~95N / mm 2 In order to ensure the control of the strip shape, the present invention strictly controls various parameters of the intermediate rolling process and the finishing rolling process, laying a foundation for subsequent strip shape control and internal stress control.

[0030] Preferably, the processing rate of the finished product rolling of the present invention is 10% to 30%, and the unit tension range of the unwinding is 40 to 60 N / mm 2 , the winding unit tension range is 45~65N / mm 2 This processing rate is used to control the strip shape tolerance, and the strip warping height is controlled below 0.06μm.

[0031] Preferably, the stress relief annealing of the present invention is bell furnace annealing, the annealing temperature is 100-300°C, and the annealing time is 2-8h. Compared with cold drawing and straightening, stress relief annealing can promote the slip of dislocations, and under low temperature heating conditions, the grains will not grow abnormally, and finally achieve the purpose of uniform stress distribution in the strip. When the annealing temperature is higher than 300°C, the strip recrystallizes and grows, and some abnormally grown grains appear; when the temperature is lower than 100°C, the driving force is not enough to drive the dislocations to slip, and there is no obvious change in the internal stress of the strip. Therefore, 100-300°C is selected as the annealing temperature and 2-8h is selected as the annealing time for stress relief annealing.

[0032] The third aspect of the present invention also provides the use of the copper alloy strip in parts such as lead frames and temperature equalizers. The copper alloy strip of the present invention has strength, electrical conductivity and stress relaxation resistance, and has a good plate shape and low warpage height, and is suitable for the preparation of various etching-processed lead frames, temperature equalizers and other parts.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] (1) Based on the Cu-Ni-P material, the present invention combines a specific deformation heat treatment process to control the proportion of large-angle and small-angle grain boundaries inside the strip, reduce the internal stress of the strip, and improve the plate shape of the strip, ultimately obtaining a strip with good stress relaxation resistance, excellent strength and conductivity, good plate shape, and low warping.

[0035] (2) The present invention forms a nickel-phosphorus phase and an iron-phosphorus phase composite reinforced copper matrix by adjusting the composition and addition ratio of the alloy, thereby making up for the shortcoming that a single strengthening method cannot take into account the material strength, electrical conductivity and stress relaxation resistance.

[0036] (3) The copper alloy strip of the present invention has a tensile strength of 600-780 MPa, a conductivity of 60-70% IACS, a high temperature softening temperature of ≥510°C, and a stress relaxation rate of ≤15% after treatment at 120°C for 1000 h under the condition of 80% of the initial stress Rp0.2, and a warpage height of less than 0.06 μm. The copper alloy strip is suitable for preparing various etching-processed lead frames, temperature balancing plates and other parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a metallographic photograph of Example 1 (magnification 500×).

[0038] Figure 2 This is the EBSD analysis test result diagram of the small-angle grain boundary and large-angle grain boundary of Example 1. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below with reference to the accompanying drawings.

[0040] The present invention selects 10 embodiments and 13 comparative examples for illustration, and the weight percentage of the chemical components of each embodiment and comparative example is shown in Table 1.

[0041] The preparation of the embodiment comprises the following preparation steps:

[0042] (1) Smelting: According to a specific order of adding materials, casting is carried out after the components are tested and qualified. During the smelting process, the surface of the molten copper is always covered with charcoal with a thickness of more than 10 cm, and the charcoal is fully baked before use. The order of adding materials for smelting is: first add the electrolytic copper plate, then add the nickel plate and copper-iron master alloy with the required components, then heat it to 1200-1300°C, and after they are all melted, perform air blowing and deoxidation. Then add the phosphor copper master alloy and the copper-chromium master alloy, and finally add the copper-magnesium master alloy. After the components meet the requirements, it is ready for casting.

[0043] (2) Semi-continuous casting: casting temperature is 1150-1250°C, and casting speed is 60-120 mm / min;

[0044] (3) Hot rolling: heating temperature is 800-950°C, holding time is 2-5h, total processing rate of hot rolling is greater than 92%, and final rolling temperature is not less than 680°C;

[0045] (4) Rough rolling: The processing volume of rough rolling shall not be less than 90%;

[0046] (5) First annealing: bell furnace annealing, annealing temperature is 420-580°C, annealing time is 4-10h;

[0047] (6) Medium rolling: The processing volume range is 60% to 85%, and the unwinding unit tension range is 60 to 80 N / mm 2 , the winding unit tension range is 80~100N / mm 2 ;

[0048] (7) Second annealing: air cushion furnace expansion annealing, heating temperature is 700 ~ 850 ℃, belt speed is 15 ~ 30m / min.

[0049] (8) Finishing rolling: The processing range of finishing rolling is 30% to 50%, and the unit tension range of unwinding is 80 to 90 N / mm 2 , the winding unit tension range is 85~95N / mm 2 .

[0050] (9) Third annealing: bell furnace annealing, annealing temperature is 340-480°C, annealing time is 4-10h;

[0051] (10) Finished product rolling: The processing amount of finished product rolling is 10% to 30%, and the unit tension range of unwinding is 40 to 60 N / mm 2 , the winding unit tension range is 45~65N / mm 2

[0052] (11) Stress relief annealing: bell furnace annealing, annealing temperature is 100-300℃, annealing time is 2-8h.

[0053] The key process operation parameters of the embodiments of the present invention and the comparative examples are detailed in Table 2, and the performance test data of the alloy strip are detailed in Table 3.

[0054] The difference between Comparative Example 1 and Example 1 is that the Ni content is 2.00wt% (wherein the ratio of (Ni+Fe) / P is retained to one decimal place);

[0055] The difference between Comparative Example 2 and Example 1 is that the Fe element content is 1.000wt%;

[0056] The difference between Comparative Example 3 and Example 1 is that the P element content is 0.40wt%;

[0057] The difference between Comparative Example 4 and Example 1 is that: no Cr element is added;

[0058] The difference between Comparative Example 5 and Example 1 is that: no Mg element is added;

[0059] The difference between Comparative Example 6 and Example 1 is that the hot rolling temperature is 750°C;

[0060] The difference between Comparative Example 7 and Example 1 is that the second annealing temperature is 600°C;

[0061] The difference between Comparative Example 8 and Example 1 is that the second annealing speed is 45 m / min;

[0062] The difference between Comparative Example 9 and Example 1 is that the processing amount of intermediate rolling is 85%, and the processing amount of finishing rolling is 20%;

[0063] The difference between Comparative Example 10 and Example 1 is that the processing amount of intermediate rolling is 50%, and the processing amount of finishing rolling is 70%;

[0064] The difference between Comparative Example 11 and Example 1 is that the third annealing temperature is 320°C;

[0065] The difference between Comparative Example 12 and Example 1 is that the processing amount of finished product rolling is 35%;

[0066] The difference between Comparative Example 13 and Example 1 is that no stress relief annealing is performed.

[0067] The above-mentioned embodiments and comparative examples were analyzed in terms of tensile strength, electrical conductivity, second phase particle morphology and distribution, grain boundaries, resistance to high temperature softening, resistance to stress relaxation and warpage height.

[0068] Tensile strength: The test is carried out on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2010 Tensile test of metallic materials Part 1: Room temperature test method. The test specimen is dumbbell-shaped, the tensile specimen width is 20 mm, and the tensile speed is 5 mm / min.

[0069] Conductivity test: According to GB / T 32791-2016 Eddy Current Test Method for Electrical Conductivity of Copper and Copper Alloys, the test strip size is 100mm×100mm.

[0070] Second phase morphology detection and distribution: According to the requirements of GB / T 6394-2007 Metal Average Grain Size Determination Method, 500 times metallographic microscope photos were collected to test the second phase morphology. The test sample size was 10mm×10mm.

[0071] High-angle grain boundary and low-angle grain boundary detection: The test was carried out using a FEIVerios G4 field emission scanning electron microscope equipped with an Oxford Symmetry EBSD probe, and the test sample size was 10mm×10mm.

[0072] High temperature softening resistance test: According to the requirements of GB / T 33370-2016 Test method for softening temperature of copper and copper alloys, the sample length is 40mm and the width is 40mm.

[0073] Stress relaxation resistance test: carried out in accordance with the requirements of GB / T 39152-2020 Copper and Copper Alloy Bending Stress Relaxation Test Method, test temperature 120℃, heating time 1000h.

[0074] Warping height: EV-3020 image measuring instrument is used for testing, and the test sample size is 200mm×200mm.

[0075] The metallographic photographs and the EBSD analysis test results of the large and small angle grain boundaries of Example 1 of the present invention are as follows: Figure 1 and Figure 2 shown.

[0076] It can be seen from Comparative Example 1 that when the Ni content is 2.00 wt %, due to the high Ni content, the strength of the material does not increase significantly, but the electrical conductivity decreases due to the excessive addition of Ni.

[0077] It can be seen from Comparative Example 2 that when the Fe element content is 1.000wt%, the strength of the material increases, but the conductivity decreases significantly, and the warping height of the strip also increases to 0.15μm. This is because an iron-rich phase is formed inside the strip, causing local stress concentration inside the material.

[0078] It can be seen from Comparative Example 3 that the P content of the material is 0.40wt%, and the strip has local peeling during rolling, and the conductivity decreases significantly.

[0079] It can be seen from Comparative Example 4 that the strength and softening temperature of the material are reduced due to the lack of Cr element.

[0080] It can be seen from Comparative Example 5 that since no Mg element is added, the warping height of the material reaches 0.20 μm.

[0081] It can be seen from Comparative Example 6 that when the hot rolling temperature is 750° C., the hot rolling structure is uneven, which eventually leads to an increase in the stress relaxation rate and warping height of the strip.

[0082] It can be seen from Comparative Examples 7 and 8 that due to the difference in the second annealing temperature and the tape speed, the solid solution effect of the strip is poor, the second phase particles agglomerate, and ultimately the strength and conductivity of the strip decrease.

[0083] It can be seen from Comparative Examples 9 and 10 that due to the different processing rate designs of intermediate rolling and finish rolling, the ratio of large-angle to small-angle grain boundaries of the strip is high, and the strip undergoes obvious warping.

[0084] It can be seen from Comparative Example 11 that when the third annealing temperature is 320° C., precipitation strengthening of the nickel-phosphorus phase cannot be fully achieved, and the strength of the strip is relatively low.

[0085] It can be seen from Comparative Example 12 that when the processing amount of the finished product rolling is 35%, although the strength increases slightly, the conductivity of the strip decreases and the warping height increases.

[0086] It can be seen from Comparative Example 13 that when the strip is not subjected to stress relief annealing, the warping height of the strip will increase significantly.

[0087] Table 1 Chemical composition of alloy strips of Examples and Comparative Examples (wt%)

[0088]

[0089] Table 2 Key process parameter control of examples and comparative examples

[0090]

[0091] Table 3 Properties of alloy strips of examples and comparative examples

[0092]

Claims

1. A copper alloy strip, It is characterized in that The invention comprises the following components in percentage by weight: Ni: 0.32-1.5wt%, P: 0.05-0.3wt%, and the remainder is copper and inevitable impurities; the volume percentage L of the small-angle grain boundaries and the volume percentage H of the large-angle grain boundaries inside the copper alloy strip satisfy: 1.5≤L / H≤2.8, wherein the small-angle grain boundaries are grain boundaries with an orientation difference of adjacent grains less than 15°, and the large-angle grain boundaries are grain boundaries with an orientation difference of adjacent grains greater than 15°.

2. The copper alloy strip according to claim 1, It is characterized in that The copper alloy strip contains 0.05-0.15wt% Fe.

3. The copper alloy strip according to claim 2, It is characterized in that In the copper alloy strip, the mass ratio of Ni+Fe to P is 3.0-8.5:

1.

4. The copper alloy strip according to claim 1, It is characterized in that The copper alloy strip comprises 0.1-0.6wt% Cr and / or 0.06-0.12wt% Mg.

5. The copper alloy strip according to any one of claims 1 to 4, It is characterized in that The copper alloy strip has a tensile strength of 600-780 MPa and a conductivity of 60-70% IACS. 0.2 Under the condition of 80% of the stress relaxation rate, after treatment at 120℃ for 1000h, the warpage height is less than 0.06μm.

6. The method for preparing a copper alloy strip according to any one of claims 1 to 5, It is characterized in that The following steps are involved: Melting → semi-continuous casting → hot rolling → rough rolling → first annealing → intermediate rolling → second annealing → finishing rolling → third annealing → finished product rolling → stress relief annealing; Wherein, the third annealing is performed in a bell furnace, the annealing temperature is 340-480° C., and the annealing time is 4-10 hours.

7. The preparation method according to claim 6, It is characterized in that The heating temperature of the hot rolling is 800-950°C, the holding time is 2-5h, the total processing rate of the hot rolling is greater than 92%, and the final rolling temperature is not less than 680°C.

8. The preparation method according to claim 6, It is characterized in that The annealing temperature of the second annealing is 700-850° C., and the tape speed is 15-30 m / min.

9. The preparation method according to claim 6, It is characterized in that The processing rate of the intermediate rolling is 60-85%, and the unit tension of the unwinding is 60-80N / mm 2 , the winding unit tension is 80~100N / mm 2 The finishing rate is 30-50%, and the unwinding unit tension is 80-90N / mm 2 , the unit tension of winding is 85~95N / mm 2 .

10. The preparation method according to claim 6, It is characterized in that The processing rate of the finished product rolling is 10-30%, and the unwinding unit tension is 40-60N / mm 2 , the winding unit tension is 45~65N / mm 2 .

11. The preparation method according to claim 6, It is characterized in that The annealing temperature of the stress relief annealing is 100-300° C., and the annealing time is 2-8 hours.

12. Use of the copper alloy strip according to any one of claims 1 to 5 in preparing a lead frame or a temperature-averaging plate.

Citation Information

Patent Citations

  • Copper alloy strip for semi-etched lead frame and preparation method of copper alloy strip

    CN115287495A

  • Copper-nickel-phosphorus etching copper alloy and preparation method thereof

    CN117626052A